تكنولوجيا المعلومات والاثصالات وطرح التمكين الإلكتروني للمواطن - دوش حمزة (University Of Eloued جامعة الوادي, 2020)
This paper examines the concept of e-empowerment from the point of view of citizenship, which indicates the political participation of citizens, their accessibility and their ability to oversee government decisions. The study focuses in particular on setting standards for measuring electronic readiness for countries in the framework of achieving citizen empowerment to serve development. But we put the issue first in its theoretical context, followed by a set of models to establish empowerment through the use of information and communication technology. The paper describes current models and indicators for measuring electronic empowerment. The reports of the United Nations Economic and Social Council were reviewed in the case study of Algeria. Then the paper presents the results of the analyzes of the measurements, which show that the level of electronic empowerment is low to medium, so that we search for the most important conclusions that can be taken at the level of the local experience in Algeria.
دراسة حالة الجزائر وفقا لتقارير الأمم المتحدة
مداخلة
Keywords: المشاركة الإلكترونية; تمكين المواطن; مؤشرات التمكين; التنمية; التحكم الإلكتروني; e-participation; citizen empowerment; empowerment indicators; development; electronic control